Treatment of a intracranial stenosis with a vulnerable plaque under proximal flow reversal with balloon angioplasty and stent placement. (21st June 2011) - Gao, Michael C; Gemmete, Joseph J; Pandey, Aditya S; Chaudhary, Neeraj
Abstract : Intracranial stenosis is associated with a high risk of ischemic events, even with medical treatment. Percutaneous transluminal angioplasty and stenting (PTAS) is an accepted intervention for addressing a moderate intracranial stenosis (≥50%) that is refractory to medical treatment. Distal emboli are seen in 34% to 70% of patients on MRI diffusion weighted images post PTAS. We present a unique case of an intracranial stenosis with a vulnerable plaque treated with PTAS under proximal flow reversal to decrease the risk of possible distal embolization.